2015
DOI: 10.1177/1203475415588652
|View full text |Cite|
|
Sign up to set email alerts
|

Non-melanoma Skin Cancer in Canada Chapter 1: Introduction to the Guidelines

Abstract: This introduction describes the need for primary prevention and offers an overview of treatment options that are discussed in later chapters of the guidelines.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 79 publications
(177 reference statements)
0
4
0
2
Order By: Relevance
“…(See chapter I for general methods. 86 ) bStrength of recommendation is evaluated as strong or weak, depending on the confidence that the treatment is more helpful than the alternative(s), including nontreatment. Hence, therapies with a high level of evidence regarding efficacy may receive a weak recommendation if the risk of adverse response is high or if this risk is not well known.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…(See chapter I for general methods. 86 ) bStrength of recommendation is evaluated as strong or weak, depending on the confidence that the treatment is more helpful than the alternative(s), including nontreatment. Hence, therapies with a high level of evidence regarding efficacy may receive a weak recommendation if the risk of adverse response is high or if this risk is not well known.…”
Section: Resultsmentioning
confidence: 99%
“…Literature searches and development of graded recommendations were carried out as discussed in the accompanying introduction (chapter 1 of the Canadian NMSC guidelines). 86…”
Section: Methodsmentioning
confidence: 99%
“…The quality of the papers reviewed were scored, where appropriate, using the Grading of Recommendations Assessment, Development and Evaluation (GRADE) system, as discussed in Chapter 1. 104…”
Section: Methodsmentioning
confidence: 99%
“…Skin cancer is the most common cancer worldwide, and comprises almost 40% of incident cancers in Canada ( 4 ). Of these, almost all are NMSCs, and are largely preventable with effective sun protection ( 5 ). Recent estimates found that over 6% of NMSC cases in Canada were attributable to sun exposure at work, with the majority of these cases occurring among those in the agricultural or construction industries ( 6 ).…”
Section: Introductionmentioning
confidence: 99%